APLIKASI ARSIP ELEKTRONIK (E-ARCHIVE) PADA BADAN AKREDITASI NASIONAL SEKOLAH/MADRASAH PROVINSI JAMBI: Electronic Archive - Pariyadi; Rinaldi Pratama, Muhammad (LP2M Universitas Nurdin Hamzah, 2022)
Archives have an important role in office administration activities. The archive acts as a source of information and is also used as evidence of accountability for the implementation of activities and finances to leaders and other relevant stakeholders. So that in its management it must be carried out in an orderly and well structured manner. The purpose of this practical work research is to build an electronic archive application system at the Badan Akreditasi Nasional Sekolah/Madrasah Provinsi Jambi in order to facilitate the archiving process and retrieval of required information safely, quickly, and efficiently.This research was conducted using the Software Development Life Cycle (SDLC) waterfall model where the application development process with this method is carried out systematically and sequentially, starting with system analysis, system design, development, testing, to operation and maintenance. The electronic archive application (E-Archive) at the Badan Akreditasi Nasional Sekolah/Madrasah Provinsi Jambi was developed web-based using the PHP script language so that the archiving process can be carried out online and related files are stored digitally.